Pewne Problemy Teorii Płyt z Zebrami Jednostronnymi - Ganowicz, R.; Gołaś, J. (Engineering Transactions, 1967)
The fundamental equations of the problem are derived by means of the variational calculus. The plates under consideration satisfy the Pflüger assumptions [1]. A theorem on the reciprocity of works is derived. This is completed by singular solutions for infinite and semi-infinite plates loaded in their planes by a concentrated force Pα, Py. These solutions, together with the reciprocity theorem are made use of for the construction of certain solutions of boundary-value problems for the plates under consideration.